2023
DOI: 10.3390/fi15070241
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of ICS and SCADA Systems Attacks Using Honeypots

Abstract: Supervisory control and data acquisition (SCADA) attacks have increased due to the digital transformation of many industrial control systems (ICS). Operational technology (OT) operators should use the defense-in-depth concept to secure their operations from cyber attacks and reduce the surface that can be attacked. Layers of security, such as firewalls, endpoint solutions, honeypots, etc., should be used to secure traditional IT systems. The three main goals of IT cybersecurity are confidentiality, integrity, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 18 publications
0
7
0
Order By: Relevance
“…For example, an attacker can alter the temperature sensor readings and send inaccurate data to the control system. Actual temperatures deviate from the perceived values, potentially leading to equipment malfunctions, product defects, or safety hazards 45 . In literature, it has been observed that researchers have made an effort to study integrity attacks on ICS from multiple dimensions.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, an attacker can alter the temperature sensor readings and send inaccurate data to the control system. Actual temperatures deviate from the perceived values, potentially leading to equipment malfunctions, product defects, or safety hazards 45 . In literature, it has been observed that researchers have made an effort to study integrity attacks on ICS from multiple dimensions.…”
Section: Resultsmentioning
confidence: 99%
“…Actual temperatures deviate from the perceived values, potentially leading to equipment malfunctions, product defects, or safety hazards. 45 In literature, it has been observed that researchers have made an effort to study integrity attacks on ICS from multiple dimensions. The authors, Do et al, 8 Min/Max attacks are the mathematical ways of modeling simple IntA.…”
Section: Simple Attacksmentioning
confidence: 99%
“…These challenges range from human errors and insuffi-cient resources for physical devices to proprietary protocols and insecure legacy systems. Insecure legacy control interfaces, connections to the internet, connected industrial IoT (IIoT) devices, and various bring-your-own devices (BYODs) [23], along with accidents due to negligence and equipment failures [24], can all serve as entry points to the systems for cyberattacks, introducing vulnerabilities. In addition, unprotected virtual machines, the unavailability of cloud infrastructure [25], account or service traffic hijacking [26], security concerns of industrial automation and analysis devices, inadequate software security mechanisms in many industrial sensors running real-time processes [23], and the omission of proper backdoor capabilities by some manufacturers for managing and updating industrial devices [27] are significant vulnerability factors that organizations need to consider after transitioning to a cloud-based infrastructure.…”
Section: Cloud-based Scada Systems Vulnerabilitiesmentioning
confidence: 99%
“…Another factor contributing to the vulnerability of cloud-based SCADA systems to various security threats is the lack of protection in some traditional SCADA communication protocols, such as Modbus/TCP , International Electrotechnical Commission (IEC) 60870-5 series, IEC 61850, and DNP3 [15]. These protocols do not support authentication and encryption mechanisms [4,23] and suffer from a lack of protection controls [2]. As a result, these protocols expose system applications running on the cloud to attackers and permit intruders' easy access to private credentials, such as IP addresses and usernames, during cloud use.…”
Section: Scada Protocols Securitymentioning
confidence: 99%
See 1 more Smart Citation